(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The efficacy of an actinomycete strain JB66 recovered from a sand dune soil from the Bikaner district of the Thar desert in inhibiting the growth of various bacterial pathogens was studied. The type strains Staphylococcus aureus, Shigella flexneri, Klebsiella pneumoniae and the clinical isolates Escherichia coli, multidrug-resistant S. aureus and P. vulgaris were included in the antimicrobial assays. Polyphasic characterization of JB66 isolate revealed its identity as Streptomyces (MH762010). It showed 88.99-89.24% sequence similarity with the other members of this genus and share the maximum (88.89%) similarity with Streptomyces sp. ATSC13. The strain JB66 was found to produce a high amount of extracellular L-asparaginase, catalase, gelatinase, protease, tyrosinase and urease enzymes. The partial chemical categorization of the methanolic crude extract of the JB66 strain led to the preliminary identification of various metabolic compounds. The thin-layer chromatography fractionation revealed the presence of prodigiosin pigment or chandramycin, cephalosporin or zeatin, daidzein, demethoxy rapamycin, 4,6-dihydroxy-7-methoxyisoflavone, munumbicins and amiclenomycin like compounds. Bio-autography revealed that the metabolites localized at the Rf values of 0.40, 0.46 and 0.53 in TLC profile had the actual bioactive fractions. UV-VIS spectrum absorbance maxima at 288 nm revealed the presence of an aromatic nucleus.